Comparative Evaluation between Sulfasalazine Alone and in Combination with Herbal Medicine on DSS-Induced Ulcerative Colitis Mice. (6th September 2017) - Shin, Mi-Rae; Kim, Kyeong Jo; Kim, Soo Hyun; Kim, Su Ji; Seo, Bu-Il; An, Hyo-Jin; Roh, Seong-Soo
Abstract : The present study aimed to investigate the comparative evaluation of pharmacological efficacy between sulfasalazine alone and sulfasalazine in combination with herbal medicine on dextran sodium sulfate- (DSS-) induced UC in mice. Balb/c mice received 5% DSS in drinking water for 7 days to induce colitis. Animals were divided into five groups (n = 9 ): Group I (normal group), Group II (DSS control group), Group III (DSS + sulfasalazine (30 mg/kg)), Group IV (DSS + sulfasalazine (60 mg/kg)), and Group V (DSS + sulfasalazine (30 mg/kg) + Cinnamomi Cortex and Bupleuri Radix mixture (30 mg/kg) (SCB)). Colonic pathological changes were analyzed using hematoxyline/eosin staining. The antioxidant, inflammatory, and apoptotic protein levels were determined using western blotting. SCB supplementation, as well as sulfasalazine, suppressed colonic length and mucosal inflammatory infiltration. In addition, SCB treatment significantly reduced the expression of proinflammatory signaling molecules through suppression of both mitogen-activated protein kinases (MAPK) and nuclear factor-kappa B (NF-κ B) signaling pathways and prevented the apoptosis of the colon. Moreover, SCB administration significantly led to the upregulation of antioxidant enzymes including SOD and catalase. Taken together, SCB treatment might offer a better treatment for human UC than sulfasalazine alone or may be useful as an alternative therapeutic strategy against UC, without any evidence of side effects.